The incidence of the host galaxy in microvariability observations of quasars - Cellone, Sergio Aldo (2000)
The incidence of a host galaxy in aperture photometry of active galactic nuclei is studied by means of actual and simulated CCD observations. Our goal is to evaluate the importance of spurious variations, introduced by seeing fluctuations during the observations, in the differential light curves used to study optical microvariability. Repeated CCD observations during two consecutive nights were used to obtain time-resolved aperture photometry for the BL Lac object PKS 2316-423, which is located at the center of a conspicuous elliptical galaxy, and for several field stars. The blazar seems to be variable according to standard variability criteria; however we show that the observed differential magnitude variations are strongly correlated with seeing fluctuations during the nights. Moreover, another galaxy within the same CCD field shows nearly identical variations, clearly indicating that such variations are artifacts of the aperture photometry. Simulated observations of quasars within host galaxies of different morphologies and spanning a wide range of luminosities were also used to evaluate the effects of changing seeing conditions. The results show that spurious differential magnitude variations due to seeing fluctuations are larger for active nuclei within brighter hosts, particularly when small photometric apertures (about the seeing FWHM in radius) are used. According to our results, several recommendations are given to future observers.